2022
DOI: 10.1136/jitc-2022-005669
|View full text |Cite
|
Sign up to set email alerts
|

Systemic cellular viroimmunotherapy for canine high-grade gliomas

Abstract: BackgroundOncolytic viruses constitute a growing field of interest, both in human and veterinary oncology, given that they are particularly helpful for treating non-surgical tumors and disseminated cancer, such as high-grade gliomas. Companion dogs present malignant gliomas with biological, genetic, phenotypic, immunological, and clinical similarities to human gliomas. These features favor comparative approaches, leading to the treatment of canine oncological patients to achieve translational applications to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…To bypass hurdles associated with non-surgical tumors and improve systemic effects, autologous canine mesenchymal stem cells can be infected with a canine oncolytic adenovirus and administered to patients. This was performed on 27 dogs with extracranial cancer and assessed by the same group in 10 subsequent dogs with high-grade gliomas ( 34 , 35 ). In the initial trial, peripheral immune cells including NK cells increased after each dose, although the changes were not statistically significant ( 34 ).…”
Section: Nk Cells In Canine Immunotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…To bypass hurdles associated with non-surgical tumors and improve systemic effects, autologous canine mesenchymal stem cells can be infected with a canine oncolytic adenovirus and administered to patients. This was performed on 27 dogs with extracranial cancer and assessed by the same group in 10 subsequent dogs with high-grade gliomas ( 34 , 35 ). In the initial trial, peripheral immune cells including NK cells increased after each dose, although the changes were not statistically significant ( 34 ).…”
Section: Nk Cells In Canine Immunotherapymentioning
confidence: 99%
“…In the initial trial, peripheral immune cells including NK cells increased after each dose, although the changes were not statistically significant ( 34 ). In the subsequent trial, dogs with gliomas received eight weekly treatments of cellular virotherapy ( 35 ). Using CIBERSORT analysis of bulk-RNAseq on tumor tissue, they found that NK cell fractions were not changed between responders and non-responders post-treatment ( 35 ).…”
Section: Nk Cells In Canine Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…(cancerous) (Cloquell et al, 2022;Sayour et al, 2018) Lymphomas (Burton et al, 2018;Gavazza et al, 2013;Sorenmo et al, 2011) Melanomas (Alexander et al, 2006;Barbosa et al, 2023;Forsberg et al, 2023;Riccardo et al, 2019Riccardo et al, , 2022Saellstrom et al, 2021) Sarcomas (Borgatti et al, 2017;Decker et al, 2017;Halpert et al, 2017;Hay et al, 2022;Judge et al, 2020;Ligon et al, 2023;Mason et al, 2016;Sahora et al, 2012;Tierce et al, 2021) General cancer (Frazier et al, 2014;Janku et al, 2016;Mason et al, 2021;Monjazeb et al, 2013;Roberts et al, 2014;Rusk et al, 2006;Saba et al, 2016;Schuh et al, 2017; Spinal cord injury (Granger et al, 2012;Prager et al, 2022) Hemophilia (Callan et al, 2016) Primary corneal endothelial degeneration (Michalak et al, 2022) Epilepsy (Patterson et al, 2020) Antiparasitic agents (Cotreau et al, 2003) Gingivitis (Arzi et al, 2020) Gliomas (non cancerous) (Bentley et al, 2018)…”
Section: Gliomasmentioning
confidence: 99%